DYKE-DAVIDOFF-MASSON SYNDROME: MYOCLONIC SEIZURES AND HEMIHYPERTROPHY IN LATE CHILDHOOD: A CASE REPORT - Halil Ural Aksoy; Senem Ayça; Celil Yılmaz; Muzaffer Polat (MNJ (Malang Neurology Journal), 2022)
Dyke-Davidoff-Masson Syndrome (DDMS) is a rare syndrome characterized with specific clinical and radiological findings due to involvement of the developing brain with cerebral hemiatrophy of one hemisphere. The syndrome was first described from Dyke, Davidoff and Masson in 1933 in a series of nine patients. Syndrome has two forms, congenital and acquired forms and etiological factors vary due to involvement of the brain. Most common clinical symptom are focal or secondary generalized seizures. Hemiparesis, facial asymmetry, intellectual disability, mental retardation, and hemihypertrophy also seen in clinical process. In magnetic resonance imaging (MRI) DDMS has unique radiological findings. Seizures are commonly refractory to treatment and aim of the treatment is to control seizures and improve mental and intellectual capabilities. Prognosis is good when clinical findings occur after two years old.